Application of two-lever baglog pressing machine technology to improve the production of oyster mushroom cultivation - Damayanti, Retno; Malin Sutan, Sandra; Hendrawan, Yusuf (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
The baglog pressing process in the Ngadi Oyster Mushroom Cultivation Community Group is still done manually, by compressing the media in a plastic bag with a bottle or plastic pipe several times until it is solid. This work requires quite a lot of labor and a long time, also depends on the skills and accuracy of the workers. Problems that can be identified in SMEs are the division of labor duties for the pressing and steaming processes, the lack of experienced workers who can compact baglog properly. So it is necessary to apply a two-lever baglog pressing machine which aims to increase production capacity. The results of the activity show an increase in baglog production capacity, from 60 baglog/day with 2 workers to 300 baglog/day with a baglog press machine. This capacity meets the needs for the steaming process, where the steamer capacity owned by SMEs is 215 baglogs/day.